RECIPE DEVELOPMENT AND TECHNOLOGY FOR SOFT CHEESE WITH APPLICATION OF VEGETABLE RAW MATERIALS - A. V. Borisova; E. S. Komarova; D. A. Belyakov; C. A. Myshova; A. V. Sergeeva (Современная наука и инновации)
Due to the high content of fats, moisture and fairly intense breakdown of proteins, soft cheeses have a creamy or curdled consistency. The production of such cheeses with the use of various vegetable additives allows you to make the product more piquant and possessing high nutritional value.